IMPLEMENTASI KEBIJAKAN SISTEM ZONASI PADA PENERIMAAN PESERTA DIDIK BARU (PPDB) 2019/2020 DI KOTA YOGYAKARTA - M. Hanif Satria Budi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2021)
The acceptance of new students (PPDB) using the zoning system was first implemented in Yogyakarta in 2018/2019. This zoning system aims to equalize education and improve the quality of education. This research was conducted to find out how the zoning system policy in Yogyakarta city under the auspices of the Yogyakarta City Education Office. This research uses qualitative approach with case study method. The results of the study showed that the zoning system in Yogyakarta has changed from the previous year. In 2019/2020 the zoning system provides a 10% chance of superior seeds, 30% of school zones, 10% of poor learners, 40% of quality pathways, 5% of out-of-school zoning pathways, and 5% of special pathways such as prospective learners whose parents moved from other regions to Yogyakarta. With this zoning system, the whole community has the opportunity to get a good quality education.